Metodologi Hukum Islam: Studi tentang Integrasi Wahyu, Sunnah, dan Ketetapan Nabi Muhammad SAW dalam Pengembangan Hukum - Suaidi, Ahmad (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2025)
This article discusses Islamic legal methodology as a framework for understanding and applying law derived from revelation, Sunnah, and the Prophetic approval (Taqrīr) in an integrated manner. Revelation provides fundamental principles and moral guidance, while the Sunnah details practical aspects of general provisions, and the Prophetic approval affirms social practices consistent with Sharia. The integration of these three sources enables Islamic law to be applied consistently, flexibly, and in a manner relevant to the evolving life of Muslim communities. A comprehensive understanding of revelation, Sunnah, and Prophetic approval ensures legal consistency and legitimacy, while also providing guidance for the performance of worship and social interactions. This approach emphasizes that Islamic law is not only normative but also practical, adaptive, and contextual. Consequently, an integrative Islamic legal methodology serves as a foundation for bridging normative principles with real-world practice, ensuring that the law remains relevant while guiding the moral, social, and spiritual life of the community across time.